PENINGKATAN PELESTARIAN BAHASA DAERAH DALAM RANGKA PEMBINAAN BAHASA INDONESIA - ROSTINA . (JURNAL ILMIAH KOHESI, 2022)
Preserving the regional language is inseparable from the language situation in Indonesia. The language situation reflectshow diverse the issue of language is. The language problem can be identified into 3 main problems, namely Indonesian /national problems, regional language problems, and foreign language problems. The three main problems have differentdimensions according to their respective positions and functions. The preservation of regional languages is not only in theform of vocabulary richers, but the refinement of regional languages as a communication system for speakers.For this reason, research on various aspects of language needs to be continuously improved for the provision of coachingfacilities, as well as dictionary and grammar in the regional language preservation series. The direction of the regionallanguage preservation policy, in the sense of regional language development in the framework of the development ofIndonesian in national cultural treasures. Preservation in the sense of regional language development requires increasedresearch, study, and development of regional languages and literature needs to be accompanied by its disseminationthrough various media. The position of the regional language in national life is certainly the basis of regional culture which inturn is a contributor and richest element of our national culture.